DESKRIPSI MINAT DAN PERILAKU PENGENDARA TRANSPORTASI ANGKUTAN BARANG DI KAWASAN MAMMINASATA - Harun, A. Muh. Yusuf; Ali, M. Ichsan; Pertiwi, Nurlita (UNM Environmental Journals, 2025)
Regional development is highly dependent on the effectiveness of transportation systems, particularly freight transport, which plays a strategic role in logistics distribution and economic growth. This study aims to describe the interest and behavior of freight vehicle drivers in the Mamminasata Metropolitan Area (Makassar, Gowa, Maros, Takalar), as well as to identify the factors influencing environmentally conscious driving behavior. A descriptive quantitative approach was employed through a survey of 200 drivers of trucks, containers, and heavy vehicles. The results show that drivers’ interest in driving safety is relatively high, while their economic interest falls into the moderate category, indicating a tendency to prioritize short-term income gains despite potential negative impacts on infrastructure and the environment. In terms of behavior, most drivers demonstrate moderate levels, with pre-trip and vehicle control behaviors rated as good, while shifting behavior, tactical behavior, and operational practices still require improvement. These findings highlight the importance of education and policy-based interventions to promote safe, efficient, and sustainable driving behavior, contributing to the development of environmentally friendly freight transport management in metropolitan areas.